Linking Technology and Reflective Practice in Primary ELT Teacher Education - García Esteban, Soraya; García Laborda, Jesus (Onomázein, 2018)
This paper presents the qualitative results of a study on the use of technology based dialogic interaction in Primary ELT teacher education. In this research technology was focused on its use to support and act as an elaborative interface in the dialogic interaction between the teacher educators and the teacher learners by (1) providing support for analysis, (2) enhancing social interaction through richer contextualization and (3) favouring the design of new teacher training materials. In this research two teacher educators at the Faculty of Education of Universidad de Alcalá (Madrid, Spain) studied the interactions of their own student teachers in microteaching activities for their own classmates, recorded the teaching-trainee-teaching-trainee and teaching-trainee-teacher interactions, and had a dialogic intervention after watching the recordings. Results indicated that dialogic interaction in the zone of proximal development (ZPD) leads to a general learning improvement along with a better self-image and higher motivation. This is due to a significant reduction of performance anxiety, the development of teaching skills, and capacity to self-observe and reflect on their own performance.